The Integrated Respiratory Physician Associate Fellowship: improving respiratory patient outcomes across primary care and secondary care - Kavita Desai; Dina Bateman (Future Healthcare Journal)
Introduction: Asthma accounts for 2–3% of primary care consultations and 60,000 hospital admissions yearly, while chronic obstructive pulmonary disease (COPD) leads to 1.4 million GP visits and is the fourth leading cause of death globally.1,2 The high prevalence of these conditions underscores the need to improve patient management, reduce admissions and lower mortality. The Integrated Respiratory Physician Associate (PA) Fellowship pilot aimed to enhance outcomes through a cross-systems PA at the Willows Practice and Primary Care Network (PCN), focusing on patients with asthma and COPD. A monthly integrated multidisciplinary team (MDT) meeting was created to optimise care and reduce secondary referrals. Materials and methods: Over 9 months, the PA reviewed 382 patients with asthma and COPD in ∼100 clinics. Data recorded included appointment type, Asthma Control Test (ACT) score or Medical Research Council (MRC) dyspnoea score, pulmonary rehabilitation or smoking cessation referrals, medication changes and multidisciplinary team (MDT) referrals. Of these patients, 34 were discussed in seven monthly integrated respiratory MDTs. Common reasons for MDT referrals included overlapping asthma and COPD diagnoses, frequent exacerbations, unclear or incorrect diagnoses, poor disease control, and overuse of short-acting beta agonists (SABA). Outcomes for MDT-discussed patients were also tracked. Results and discussion: 8 out of 34 patients discussed in MDTs (Fig 1) had incorrect diagnoses removed, and 15 underwent further investigations (eg, spirometry and reversibility testing, FeNO, assessment for breathing pattern disorder, etc) (Fig 2). Long-term PA integration could reduce secondary care referrals and help primary care networks (PCNs) meet annual Quality and Outcomes Framework (QOF) targets. Conclusion: Feedback from a post-fellowship colleague questionnaire revealed significant improvements in asthma and COPD outcomes due to the PA role, enhancing care management and co-ordination. There is strong support for expanding this integrated PA model to other specialties to further elevate patient care. Challenges related to role awareness, continuity of care and clinic booking can be addressed through ongoing role development.